The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jbiomech.2017.08.025
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations of musculoskeletal models for a more accurate estimation of lower limb joint contact forces during normal gait: A systematic review

Abstract: Musculoskeletal modelling is a methodology used to investigate joint contact forces during a movement. High accuracy in the estimation of the hip or knee joint contact forces can be obtained with subject-specific models. However, construction of subject-specific models remains time consuming and expensive. The purpose of this systematic review of the literature was to identify what alterations can be made on generic (i.e. literature-based, without any subject-specific measurement other than body size and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 60 publications
4
27
0
Order By: Relevance
“…This is the level of concordance already reported for more comprehensive muscle geometries (Giroux et al, 2013). The errors in the proximaldistal tibiofemoral contact force fell in the range of RMSEs (0.3 to 0.9 BW) reported in the literature with generic musculoskeletal models (Moissenet et al, 2017). As for the RMSEs on the force peaks, they range between 0.06 and 1.10 BW and match the typical errors (0.1 to 1.7 BW) reported with musculoskeletal models using numerical optimisation (DeMers et al, 2014;Knarr and Higginson, 2015;Thelen et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is the level of concordance already reported for more comprehensive muscle geometries (Giroux et al, 2013). The errors in the proximaldistal tibiofemoral contact force fell in the range of RMSEs (0.3 to 0.9 BW) reported in the literature with generic musculoskeletal models (Moissenet et al, 2017). As for the RMSEs on the force peaks, they range between 0.06 and 1.10 BW and match the typical errors (0.1 to 1.7 BW) reported with musculoskeletal models using numerical optimisation (DeMers et al, 2014;Knarr and Higginson, 2015;Thelen et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…Only a preliminary validation (errors on proximal-distal tibiofemoral contact force peaks below 10% during gait) has been reported using the data of one subject with an instrumented prosthesis (Messier et al, 2013). This reported level of error, below 10%, compares favourably with the errors obtained with numerical optimisation (Moissenet et al, 2017). However, this preliminary validation was performed on one subject and was limited to peak values of the proximal-distal tibiofemoral contact force.…”
Section: Introductionmentioning
confidence: 95%
“…There are some limitations and uncertainties related to MS models and several parameters influences the joint loads (Moissenet et al 2017). As shown in this study, the joint loads are highly affected by the surrounding muscles so the chosen muscle parameters have a big impact on the load reduction.…”
Section: Discussionmentioning
confidence: 92%
“…The computational simulation of human motion using musculoskeletal modeling has been performed in a number of studies to investigate musculo-tendon forces and joint contact forces, which cannot be easily achieved by physical measurements [25], [27], [29]. Recent studies have demonstrated that personalization of model parameters, such as the size of the bones, geometry of the muscles and tendons, and physical properties of the muscle-tendon complex, improves accuracy of the simulation [4], [20], [32]. While the majority of previous studies modeled the musculo-tendon unit as one or multiple lines joining their origin and insertion, including so-called via points in some cases, several recent studies have shown that volumetric models representing subject-specific muscle geometry provide higher accuracy in the simulation [37].…”
Section: Introductionmentioning
confidence: 99%